[3, 3]‐Sigmatropic Rearrangement Step in the Gold‐Catalyzed Cyclization of Allyl‐(ortho‐alkinylphenyl)methyl Ethers. Issue 8 (31st May 2013) - Ackermann, Martin; Bucher, Janina; Rappold, Melissa; Graf, Katharina; Rominger, Frank; Hashmi, A. Stephen K.
Abstract The gold‐catalyzed conversion of allyl‐(ortho‐alkynylphenyl)methyl ethers was investigated, and allylated isochromenes were obtained. An optimization of the catalysis conditions with respect to different phosphane and carbene ligands on gold, different counterions, and different solvents was conducted. Subsequently, the scope and limitations of this reaction were investigated with 21 substrates. The mechanistic studies show an allylic inversion, as supported by NMR data and an X‐ray crystal structure analysis, as well as an intermolecular reaction, as determined by crossover experiments. There is no competition of protodeauration even in the presence of water. All these observations differ from other related conversions and clearly indicate product formation by a [3, 3]sigmatropic rearrangement in the step forming the new CC bond.